Preparation of thin layer CuO from Cu2O using the Spin Coating Method at Various Annealing Temperature and Number of Dripping for Photoelectrochemical Water Splitting - Eka Pratista; Gunawan Gunawan; Didik Setiyo Widodo (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
A thin layer preparation of CuO from Cu2O powder using Fehling's solution for photoelectrochemical applications has been performed. The research was focused on studying the effect of annealing temperature and the number of drops on the performance of CuO thin layer semiconductors from Cu2O powder prepared by spin coating with a rotation rate of 500 rpm for 15 seconds. The thin layers were treated with annealing with temperature variations of 300°C, 400°C, and 500°C for 1 hour and variations in the number of drops of 10, 20, and 50 drops. The CuO thin layer was tested in a photoelectrochemical process as a photocathode to split water with a simulated light of 1.5 AM (100 mW/cm2). The process of splitting water as a method of producing hydrogen energy by photoelectrochemistry is assisted by semiconductors, such as CuO, in an electrolyte solution to capture photons and drive the water-splitting reactions. Copper (II) Oxide (CuO) is a p-type semiconductor with a band gap of 1.2-2.5 eV, which can be used as a photocathode. The optimum photoelectrochemical measurement results were obtained at an annealing temperature of 400°C and 50 drops with a current density of 0.584 mA/cm2 at a potential of 0.2 V versus the Reversible Hydrogen Electrode (RHE). The results of the Scanning Electron Microscopy (SEM) analysis show that the morphology of the oxide is spherical. Energy dispersive X-ray (EDX) analysis displays that the sample contained 51.46% and 48.54% of Cu and O, respectively. The X-ray diffraction pattern (XRD) analysis shows that the oxide grain size is 44.137 nm.